3D whole‐heart isotropic‐resolution motion‐compensated joint T1/T2 mapping and water/fat imaging. Issue 6 (16th June 2020) - Milotta, Giorgia; Bustin, Aurelien; Jaubert, Olivier; Neji, Radhouene; Prieto, Claudia; Botnar, René M.
Abstract : Purpose: To develop a free‐breathing isotropic‐resolution whole‐heart joint T1 and T2 mapping sequence with Dixon‐encoding that provides coregistered 3D T1 and T2 maps and complementary 3D anatomical water and fat images in a single ~9 min scan. Methods: Four interleaved dual‐echo Dixon gradient echo volumes are acquired with a variable density Cartesian trajectory and different preparation pulses: 1) inversion recovery‐preparation, 2) and 3) no preparations, and 4) T2 preparation. Image navigators are acquired to correct each echo for 2D translational respiratory motion; the 8 echoes are jointly reconstructed with a low‐rank patch‐based reconstruction. A water/fat separation algorithm is used to obtain water and fat images for each acquired volume. T1 and T2 maps are generated by matching the signal evolution of the water images to a simulated dictionary. Complementary bright‐blood and fat volumes for anatomical visualization are obtained from the T2 ‐prepared dataset. The proposed sequence was tested in phantom experiments and 10 healthy subjects and compared to standard 2D MOLLI T1 mapping, 2D balance steady‐state free precession T2 mapping, and 3D T2 ‐prepared Dixon coronary MR angiography. Results: High linear correlation was found between T1 and T2 quantification with the proposed approach and phantom spin echo measurements ( y = 1.1 × −11.68, R 2 = 0.98; and y = 0.85 × +5.7, R 2 = 0.99). Mean myocardial values of T1 /T2 = 1116 ± 30.5 ms/45.1 ± 2.38 ms were measured in vivo. Biases of T1 /T2 = 101.8 ms/−0.77 ms were obtained compared to standard 2D techniques. Conclusion: The proposed joint T1 /T2 sequence permitted the acquisition of motion‐compensated isotropic‐resolution 3D T1 and T2 maps and complementary coronary MR angiography and fat volumes, showing promising results in terms of T1 and T2 quantification and visualization of cardiac anatomy and pericardial fat.